Tailoring care for advanced COPD - Chatila, Wissam (Henry Stewart Talks, 2016)
COPD case study, Combined assessment of COPD, Therapeutic options: COPD medications, Advantages, limitations, and concerns about available therapy for COPD, Combination therapies, Risk factors for progression, COPD exacerbations, and complications with current therapy, Update talk: COPD medications, Update talk: Mono vs. dual vs. triple therapy in COPD, Update talk: Role of ICS in COPD
Updated at 2021/09/30